The meaning of feedback: medical students’ view - Pricinote,Silvia Cristina Marques Nunes (2021)
Abstract: Introduction: The teaching-learning process in health involves a binomial: on the one hand, teaching (the teacher and the institution) and, on the other hand, the students and their ability to adequately interact in this context. Just as teaching requires specific skills, learning also requires students to be able to master the necessary skills for learning. Feedback should also be understood in this regard. Although feedback is a frequent topic in the literature, few studies have addressed its meaning and impact from the students’ perspective. Moreover, a gap has been identified between theory and practice regarding the real power of feedback in the teaching-learning process. Objective: This study aimed to assess medical students’ understanding of feedback. Method: This is a qualitative research with a descriptive and exploratory focus, carried out using in the case study modality, with the focus group technique in data collection and thematic content analysis. The participants were medical students attending the fourth-year or eighth-semester at three schools located in the state of Goiás, Brazil. Results: The following categories emerged: understanding of feedback, frequency of received feedback, impact of feedback on the teaching-learning process and perception about the received feedback. Students understood in part the concept of feedback, not recognizing the internal feedback. A low frequency of feedback was reported and depended on the teacher, subject and year/semester of the course related to the type of curriculum. Even so, the participants recognized the points of feedback that impact on the teaching-learning process and were receptive to effective feedback. Conclusion: Even though they knew the meaning of feedback only partially and experienced it irregularly, medical students recognized the impact of this tool on the teaching-learning process. In a context of students trained to know about their own knowledge, truly empowering them in the teaching-learning process, they will develop a constant reflective practice of generating internal feedback, allowing the actual impact of feedback on the teaching-learning process to be observed in practice, as described in the literature.